2001
DOI: 10.1038/sj.bmt.1703143
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood transplants: early recovery of neutrophils from co-transplanted sibling haploidentical progenitor cells and lack of engraftment of cultured cord blood cells, as ascertained by analysis of DNA polymorphisms

Abstract: Summary:The number of infused cells is a very important factor in cord blood transplant (CBT) engraftment. Prior ex vivo expansion of aliquots of transplanted cord blood (CB) units is being investigated as a procedure to increase engraftment potential, but results are difficult to evaluate due to a lack of markers for assessing the contribution of expanded cells. We transplanted five patients, infusing the best available CB unit and cells from a second donor simultaneously. In two patients, these cells were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 28 publications
0
38
0
2
Order By: Relevance
“…This limitation may be overcome by the co-infusion of a relatively low number of T-cell-depleted mobilized hematopoietic stem cells (MHSC) from a third-party donor (TPD). [1][2][3] Here we report results of engraftment, morbidity and survival of a total of 55 consecutive patients transplanted in our center using this strategy between March 1999 and October 2007. These data confirm and extend results reported previously on the value of the procedure to achieve high rates of engraftment and full chimerism of single unit CBT in adults after myeloablative conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation may be overcome by the co-infusion of a relatively low number of T-cell-depleted mobilized hematopoietic stem cells (MHSC) from a third-party donor (TPD). [1][2][3] Here we report results of engraftment, morbidity and survival of a total of 55 consecutive patients transplanted in our center using this strategy between March 1999 and October 2007. These data confirm and extend results reported previously on the value of the procedure to achieve high rates of engraftment and full chimerism of single unit CBT in adults after myeloablative conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6][7][8][9] These results are difficult to interpret because insufficient details are provided in any study regarding the ad hoc computational procedures followed, the accuracy of the results or whether the measurements were assessed for reliability. It is uncertain whether any previous study analyzed loci with shared alleles, despite their common occurrence in DD HSCTs.…”
Section: Introductionmentioning
confidence: 80%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] However, the complex chimeric states associated with these transplants engender novel quantitative problems for the monitoring laboratory. The most challenging issue in analyzing multi-donor chimeras is the almost universal occurrence of shared alleles, that is, STR peaks (bands) with identical alleles from more than one DNA source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernandez et al [26][27][28] reported the co-infusion of large numbers of highly purified CD34 þ progenitors from haploidentical donors in the setting of myeloablative transplantation with one UCB unit. The median time to neutrophil recovery was 10 days.…”
Section: Ucb Transplantation In Adults With Malignanciesmentioning
confidence: 99%